Irritability in children and adolescents: Contemporary perspectives and clinical implications - Stevanović, Dejan; Stevanović, Teodor (Engrami, 2024)
Although pathological irritability has long been studied, intensive research in the last twenty years has brought significant findings about its etiology and potential therapies. This overview gives the current understanding, diagnostic aspects, neuropsychobiological characteristics and treatment of irritability in children and adolescents. Irritability is understood today as an increased tendency to anger that manifests itself stably over time. Although not a disorder, irritability is a cardinal symptom of oppositional defiant disorder with chronic irritability-anger. It is also present as an associated symptom in various internalizing and externalizing disorders, and is especially associated with depression, anxiety disorders, autism, and attention deficit hyperactivity disorder (ADHD). It is assumed that it arises due to reduced tolerance to frustration and a lowered threshold for the perception of external stimuli as threatening, as well as being a hereditary feature significantly dependent on environmental influences. Treatment is based on pharmacological, non-pharmacological and combined treatments, whereby second-generation antipsychotics are proven to be the most effective. A broader understanding of irritability as a complex transdiagnostic, psychopathological phenotype of mood, cognition and behavior, and a common denominator of various disorders, has important clinical implications, especially for early recognition, correct diagnosis and effective treatment.